The "one‐point method" for estimating maximum carboxylation capacity of photosynthesis: A cautionary tale. (20th June 2019) - Burnett, Angela C.; Davidson, Kenneth J.; Serbin, Shawn P.; Rogers, Alistair
Abstract: The maximum carboxylation capacity of Rubisco, V c, max, is an important photosynthetic parameter that is key to accurate estimation of carbon assimilation. The gold‐standard technique for determining V c, max is to derive V c, max from the initial slope of an A – C i curve (the response of photosynthesis, A, to intercellular CO2 concentration, C i ). Accurate estimates of V c, max derived from an alternative and rapid "one‐point" measurement of photosynthesis could greatly accelerate data collection and model parameterization. We evaluated the practical application of the one‐point method in six species measured under standard conditions (saturating irradiance and 400 μmol CO2 mol −1 ) and under conditions that would increase the likelihood for successful estimation of V c, max : (a) ensuring Rubisco‐limited A by measuring at 300 μmol CO2 mol −1 and (b) allowing time for acclimation to saturating irradiance prior to measurement. The one‐point method significantly underestimated V c, max in four of the six species, providing estimates 21%–32% below fitted values. We identified ribulose‐1, 5‐bisphosphate‐limited A, light acclimation, and the use of an assumed respiration rate as factors that limited the effective use of the one‐point method to accurately estimate V c, max . We conclude that the one‐point method requires a species‐specific understanding of its application, is often unsuccessful, and must be used with caution. Abstract : The "one‐point" rapid method for estimating the maximum carboxylation capacity of Rubisco ( V c, max ) from a single measurement of photosynthesis, often requires prior acclimation to saturating light and/or measurements of day respiration in order to accurately estimate V c, max .